Taxonomy notes on Vandeae (Orchidaceae) from China: Five new species and two new records - Jian-Wu Li (KeAi Communications Co., Ltd., 2021)
Five new species (Gastrochilus yei, Gastrochilus minimus, Luisia simaoensis, Taeniophyllum xizangense, Tuberolabium subulatum) and two newly recorded species (Cleisostoma tricornutum, Luisia inconspicua) of Vandeae (Orchidaceae) from China are described and illustrated. Gastrochilus yei is similar to G. affinis and G. nepalensis, but differs from them by having an epichile not lobed, the apex of the hypochile not bilobed, and a tine on the apex of the leaf. Gastrochilus minimus is similar to G. acinacifolius, but can be distinguished from the latter by having a flabellate epichile that is densely hirsute on the adaxial surface and an inconspicuous central cushion; in addition, the hypochile of G. minimus has a keel that extends to the apex of the epichile. Taeniophyllum xizangense is similar to T. stella and T. radiatum, but it is distinguished from them by having much bigger flowers, inflorescences densely covered with short-bristly hairs, papillae on the external surface of sepals, and bigger triangular-ovate viscidium. Luisia simaoensis is similar to L. magniflora and L. ramosii, but can be easily distinguished from them by having lateral sepals longer than dorsal sepals and petals, lip with irregular and waved margins, and lip with bilobed apex. Luisia inconspicua is moved from Gastrochilus to Luisia based on phylogenetic analyses of plastid matK sequence data. Tuberolabium subulatum is similar to T. carnosum, but it can be easily distinguished from the latter by having an inflorescence much shorter than the leaves, yellow sepals and petals, and many small papillae outside the lip lobes.